2012
DOI: 10.1242/jcs.111237
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of claudin-2 on serine 208 promotes membrane retention and reduces trafficking to lysosomes

Abstract: SummaryClaudins are critical components of epithelial and endothelial tight junction seals, but their post-transcriptional regulation remains poorly understood. Several studies have implicated phosphorylation in control of claudin localisation and/or function, but these have focused on single sites or pathways with differing results, so that it has been difficult to draw general functional conclusions. In this study, we used mass spectrometry (MS) analysis of purified claudin-2 from MDCK II cells and found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 69 publications
2
61
0
Order By: Relevance
“…A large body of evidence shows that interference in the interactions between TJ proteins perturbs the TJs affecting the barrier permeability of the endothelium ( 38 ). It was further observed that the TJ formation or disintegration depends on the phosphorylation state of TJ proteins (39)(40)(41). However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama mentioning
confidence: 99%
“…A large body of evidence shows that interference in the interactions between TJ proteins perturbs the TJs affecting the barrier permeability of the endothelium ( 38 ). It was further observed that the TJ formation or disintegration depends on the phosphorylation state of TJ proteins (39)(40)(41). However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama mentioning
confidence: 99%
“…To formally prove this hypothesis, detection of KRAS phosphorylation was necessary. Since no suitable antibodies are available, we used the Phos-Tag-based approach (31,32) to determine the oncogenic KRAS phosphorylation status in the generated tumors. This method is based on the fact that a complex formation between the phosphate group of a phosphorylated protein and a divalent metal ion in Phos-Tag reduces the mobility of the phospho-protein during the electrophoresis separation, thus allowing resolution of phosphorylated and non-phosphorylated proteins into different bands.…”
Section: Pkc Inhibitors Diminish Oncogenic Kras-mediated Tumor Growthmentioning
confidence: 99%
“…Although most of the 23 human claudins end in a similar Tyr-Val canonical PDZ binding motif (see Fig. 1), their more upstream residues are both shared and distinct (6). The mechanisms that regulate claudin function remain poorly defined but of considerable interest.…”
mentioning
confidence: 99%
“…For example, the cytoplasmic tails of many claudins are documented to be phosphorylated at multiple positions including serines, threonines, and tyrosines (15). Changes in phosphorylation have been correlated with changes in barrier properties, trafficking, and turnover, cited in Van Itallie et al (6), although no direct evidence has yet been provided that phosphorylation alters affinity of the PDZ domaintarget interaction. Similar correlative findings have been reported after introducing phosphomimicking mutations (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation